In vitro Models for Studying Drug Metabolites and Metabolizing Enzymes: A Comprehensive Review - Anumolu, Durga Pani Kumar; Veena, Bugga; Afreen, Syed Sara; Bandla, Jahnavi; Lakshmi, KNV. Chenchu; Pulusu, Veera Shakar (International Journal of Pharmaceutical Investigation, 2026)
Background In vitro assays play a crucial part in evaluating the metabolic fate of drug candidates and understanding the activity of drug-metabolizing enzymes. Materials and Methods Model systems including Hepatocytes, S9 fractions, and liver microsomes are frequently employed to investigate xenobiotic metabolism and assess potential toxicity and recombinant enzymes, provide controlled environments to investigate biotransformation pathways, metabolite formation, and enzyme kinetics without the complexity of whole-animal studies. Results and Discussion The assessment of drug metabolites in vitro helps predict pharmacokinetic behavior, drug–drug interactions, and potential toxicity, thereby supporting drug discovery and development. Enzyme-specific assays further enable identifying the main isoforms of cytochrome P450 and conjugating enzymes take part in metabolism of drug. Conclusion Overall, in vitro assays of drug metabolites and enzymes involved in drug metabolism serve as essential tools in preclinical research, facilitating safer and more effective pharmaceutical development and regulatory evaluation.
Keywords: Assay; Cytochrome P450; Enzyme Kinetics; Hepatocytes; Liver microsomes; Metabolizing Enzymes; S9 fraction